(untitled) (Universal International Scientific Journal, 2026)
This article studies preprocessing algorithms aimed at effectively eliminating noise in digital images and improving image quality. During the study, the principles of operation of linear and nonlinear filtering methods were comparatively analyzed. According to the experimental results, the Gaussian filter showed high efficiency in smoothing white noise, and the Median filter showed high efficiency in eliminating impulse noise. Based on the analysis, a software package was developed using the Python programming language and the OpenCV library to filter images